2018
DOI: 10.1002/cbdv.201800030
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Antioxidant Activity of Lignans in Schisandra chinensis and Schisandra sphenanthera from Different Locations

Abstract: Twenty Schisandra samples were collected from different locations. Contents of 7 lignans in the samples were determined and analyzed by HPLC method coupled with hierarchical clustering analysis (HCA) and principal component analysis (PCA), and the antioxidant capacity of Schisandra from the different locations was evaluated by reducing power, ferric thiocyanate (FTC) and 2,2'-diphenyl-1-picrylhydrazyl (DPPH) assay. The results showed that there was a significant difference in the content of lignans between Sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 12 publications
0
16
0
1
Order By: Relevance
“…Presently, we have not been able to identify the active component responsible for the observed beneficial effects on the muscles of aged mice. SF contains many bioactive compounds including lignans, triterpenoids, flavonoids, polyphenol, and polysaccharides [43], and lignans are known to be a major component of SF [43, 44]. Accordingly, we speculated that one or some lignans might be the active compound responsible for this effect, and further studies are required to identify the active ingredients.…”
Section: Discussionmentioning
confidence: 99%
“…Presently, we have not been able to identify the active component responsible for the observed beneficial effects on the muscles of aged mice. SF contains many bioactive compounds including lignans, triterpenoids, flavonoids, polyphenol, and polysaccharides [43], and lignans are known to be a major component of SF [43, 44]. Accordingly, we speculated that one or some lignans might be the active compound responsible for this effect, and further studies are required to identify the active ingredients.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the antioxidant capacity of these compounds, studies by Wang et al [88] evaluated the ability of the extracts of S. chinensis and S. sphenanthera to scavenge the DPPH radical. The authors suggested that variations in lignan content between the extracts lead to different antioxidant activities.…”
Section: Discussionmentioning
confidence: 99%
“…The chemical composition and resulting biological activity of plant extracts depends on humidity, light, soil type, latitude, season, maturity, harvest time, geographical location, temperature, and other factors [18]. Additionally, the content of individual lignans in SCE fruits depends on the location of the crop, the degree of fruit maturity, and harvest season [19,20,21]. Zhang et al, (2009) studied ten fruit samples from different provinces of China [19].…”
Section: Biologically Active Compounds In Scementioning
confidence: 99%
“…This compound constituted 31%–33% of the Schisandra lignans in fruits originating from Korea, and 36%–46% of those from China. In eight out of ten fruit samples, tested by Wang et al, the relationship in the concentration of SCE lignans was schisandrin > gomisin A > schisandrin B [21].…”
Section: Biologically Active Compounds In Scementioning
confidence: 99%